Functional lower extremity strength influences stepping strategy in community-dwelling older adults during single and dual-task walking - Brandon M. Peoples; Kenneth D. Harrison; Keven G. Santamaria-Guzman; Silvia E. Campos-Vargas; Patrick G. Monaghan; Jaimie A. Roper (Scientific Reports, 2024)
Abstract As age increases, a decline in lower extremity strength leads to reduced mobility and increased fall risks. This decline outpaces the age-related reduction in muscle mass, resulting in mobility limitations. Older adults with varying degrees of mobility-disability use different stepping strategies. However, the link between functional lower extremity strength and stepping strategy is unknown. Therefore, understanding how age-related reductions in functional lower extremity strength influence stepping strategy is vital to unraveling mobility limitations. Twenty participants (17F, 72 ± 6 years) were recruited and tested at a local community event. Participants were outfitted with inertial measurement units (IMU) and walked across a pressurized walkway under single and dual motor task conditions (walking with and without carrying a tray with water) at their usual and fast speeds. Participants were dichotomized into normal (11) or low functional strength groups (9) based on age-specific normative cutoffs using the instrumented 5-repetition Sit-to-Stand test duration. Our study reveals that older adults with normal strength prefer adjusting their step time during walking tasks, while those with reduced strength do not exhibit a preferred stepping strategy. This study provides valuable insights into the influence of functional lower extremity strength on stepping strategy in community-dwelling older adults during simple and complex walking tasks. These findings could aid in diagnosing gait deviations and developing appropriate treatment or management plans for mobility disability in older adults.